PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI SEKOLAH DASAR - Agustinus Tanggu Daga; Aprilio Setia Budi (Jurnal Genta Mulia, 2025)
The problem of low achievement in mastering subject matter shows the need for a more effective learning model.  This study aims to determine the effectiveness of the inquiry model in influencing the science learning outcomes of V Grade students at Pogo Lede Public Elementary School. The study used a quasi-experimental design with 36 students as subjects. Data were collected through learning outcome tests before and after treatment, and analyzed using descriptive statistics and t-tests. The results showed a significant increase in the experimental group from an average of 15.22 to 76.11, while the control group only increased from 12.17 to 62.76. A significance value of 0.003 (<0.05) indicates a significant difference between the two groups. The inquiry model has proven to be effective and relevant to be implemented by teachers, supported by schools, and studied further in further research.